A native weevil and an exotic planthopper: investigating potential biological control agents for nymphaea mexicana zuccarini (nymphaeaceae) and its hybrids in South Africa - Reid, Megan Kim (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
Nymphaea mexicana Zuccarini (Nymphaeaceae) is an invasive plant originating from southern USA and Mexico that has become problematic in South Africa, invading several water bodies around the country. Manual removal of this plant is very labour intensive and is not cost efficient or effective for long term control, while the use of herbicides is damaging to the environment and expensive. Consequently, this plant is a desirable candidate for biological control, which takes advantage of enemy release of the target weed and aims to re-establish population suppression induced by host specific natural enemies. Initiating biological control requires that several steps are followed to maximise the success of the programme, and the first few of these, including overseas surveys in the native range of the plant, have already been completed. This thesis aimed to continue biological control research for this species to take further steps at effectively managing the plant. Firstly, pre-release surveys in the invaded range are necessary to: determine what factors (including enemy release) contribute to the invasiveness of the target weed; establish a baseline of information to allow for comparison after biological control agents have been released; and identify any insect herbivores that may already be present in the country. The pre-release surveys conducted in this study revealed useful information about N. mexicana invasions in South Africa and provided evidence that enemy release is applicable to this case. However, these studies determined that a native weevil, Bagous longulus Gyllenhal (Coleoptera: Curculionidae), has expanded its host range to include the exotic N. mexicana at three sites, and may thus have potential for management of the species through augmentative releases. The invasion of N. mexicana in South Africa is further complicated by the presence of several Nymphaea hybrids originating from a complex history of horticultural trade. Although previous research has shown that several hybrid groups are present in South Africa, their parentage is not known. As biological control requires the use of host specific insects adapted to overcome the unique chemical and morphological defences utilised by plant species, hybrids are notoriously difficult to manage because they possess intermediate characters inherited from parent species to which natural enemies may not have adapted. Although biological control of hybrids is challenging, other case studies have demonstrated that it is possible to find suitable agents, but the chances of success are increased if putative parents of the hybrids are known so that they can be surveyed for natural enemies. Further molecular studies including possible parents of the Nymphaea hybrids in South Africa were thus carried out in this thesis to focus future surveying efforts. Two main hybrid groups were identified with genetic similarity to two tested putative Nymphaea parents, and this will allow further investigations of these species to improve the chances of successfully managing these hybrid groups. Some of the tested hybrids showed genetic contributions from multiple groups, some of which were unidentified, so it is necessary to prioritise the most problematic hybrids for biological control. With more insight into the genetic makeup of the Nymphaea hybrids in South Africa, investigations into the host specificity of potential biological control agents can be conducted. The ideal biological control agent should have a broad enough host range to impact and survive on both N. mexicana and its hybrids, but without a host range so broad that it would pose risk to native South African species. Host specificity trials are thus necessary to determine the suitability of potential agents. The identification of B. longulus feeding on N. mexicana during pre-release surveys motivated further investigations to determine the natural distribution, field host range, and host specificity of B. longulus in experimentally controlled conditions. Further surveys were therefore conducted at native Nymphaea sites around South Africa in addition to host specificity trials using the native Nymphaea nouchali Burm. f. (Nymphaeaceae), two populations of N. mexicana, and a cultivated hybrid. Results from the surveys and host specificity tests suggest that B. longulus is widely distributed across South Africa, is specific to Nymphaea with no observed preference between N. mexicana and the native N. nouchali, and does not perform well on Nymphaea hybrids. Hence, B. longulus is promising for use in new association biological control through augmentative releases but is not suitable for management of hybrids. In addition to the potential use of the South African B. longulus, it is necessary to conduct host specificity trials for natural enemies from the native range of N. mexicana that were prioritised in previous studies. Megamelus toddi Beamer (Hemiptera: Delphacidae) is one such species that was imported into quarantined laboratory conditions from Florida, USA. Host specificity trials were conducted using the same test plants as described for the studies on B. longulus, in addition to multigeneration trials to determine how long M. toddi could survive on non-target host plants. As with the B. longulus studies, no statistically significant differences in preference were observed between N. mexicana and N. nouchali, but M. toddi could not complete development on the test hybrid, indicating that this species is also unsuitable for the management of Nymphaea hybrids. Despite suboptimal plant health, M. toddi completed development for three generations on the native N. nouchali. This lack of host specificity deems M. toddi unsafe for release in South Africa but highlights the importance of following predefined steps to develop a biological control programme. The concluding chapter of this thesis discusses the aforementioned findings in a broader context by considering the driving forces of plant invasions in general and specifically for N. mexicana in South Africa. Case studies are also consulted to provide insight into how to proceed with managing Nymphaea hybrids in South Africa, while the factors governing host specificity and host range expansion are also discussed and considered in the context of B. longulus and M. toddi. Finally, after a consideration of the limitations of these studies, recommendations are made to continue the development of biological control for N. mexicana in South Africa.
Keywords: Nymphaeaceae -- South Africa; Water lilies Biological control -- South Africa; Host specificity; Genetic variation; Bagous longulus